2017
DOI: 10.1088/2053-1583/aa8c8a
|View full text |Cite
|
Sign up to set email alerts
|

Touch-mode capacitive pressure sensor with graphene-polymer heterostructure membrane

Abstract: We describe the fabrication and characterisation of a touch-mode capacitive pressure sensor (TMCPS) with a robust design that comprises a graphene-polymer heterostructure film, laminated onto the silicon dioxide surface of a silicon wafer, incorporating a SU-8 spacer grid structure. The spacer grid structure allows the flexible graphene-polymer film to be partially suspended above the substrate, such that a pressure on the membrane results in a reproducible deflection, even after exposing the membrane to press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
(46 reference statements)
0
31
0
1
Order By: Relevance
“…[ 61,77,78 ] A heterostructure diaphragm (graphene and polymer composite materials) based TMCPS array has been fabricated on thin silicon substrate, however, any other material could be utilized in place of silicon, as the researchers proposed for future work. [ 79,80 ] Commercially available household materials, like Al‐coated polyimide (PI) foil and double‐sided tape, are utilized for designing flexible TMCPS. [ 81 ] The sensor is fabricated [Figure 3f] by cutting two circular pieces from Al‐coated PI sheet and then using three layers of double‐sided tape along the edges to paste the pieces together.…”
Section: Types Of Flexible Capacitive Pressure Sensorsmentioning
confidence: 99%
“…[ 61,77,78 ] A heterostructure diaphragm (graphene and polymer composite materials) based TMCPS array has been fabricated on thin silicon substrate, however, any other material could be utilized in place of silicon, as the researchers proposed for future work. [ 79,80 ] Commercially available household materials, like Al‐coated polyimide (PI) foil and double‐sided tape, are utilized for designing flexible TMCPS. [ 81 ] The sensor is fabricated [Figure 3f] by cutting two circular pieces from Al‐coated PI sheet and then using three layers of double‐sided tape along the edges to paste the pieces together.…”
Section: Types Of Flexible Capacitive Pressure Sensorsmentioning
confidence: 99%
“…When pressure is applied over that limit, the upper membrane deforms and the capacitance increases until the top membrane is totally collapsed. Indeed, based on the studies reported in [19]- [21], the behavior of the membrane can be simplified in two main distinct operating modes: the normal mode (region 1), when the membrane is freely suspended on the cavity and characterized by a linear and high sensitive response; the touch mode (region 2), at a pressure over a transition point (incipient touch), the membrane goes in direct contact with the base of the cavity until it totally collapses.…”
Section: Sensing Modeling and Structure Designmentioning
confidence: 99%
“…There are different ways to readout the deflection of the membrane and thereby quantify the pressure difference. In capacitive graphene pressure sensors, the deflection is readout by measuring the capacitance between the graphene membrane and a reference electrode [9][10][11][12] . As the pressure-induced deflection increases the mechanical stress and tension in the membrane, it can be measured using the piezoresistive effect [13][14][15] and can be probed via the mechanical resonance frequency 2,3,16 .…”
Section: Introductionmentioning
confidence: 99%